2007
DOI: 10.1029/2006pa001365
|View full text |Cite
|
Sign up to set email alerts
|

Climatological evaporation seasonality in the northern Red Sea

Abstract: [1] The dynamic and thermodynamic processes that underlie the exceptionally high evaporation over the northern Red Sea are examined. Through a combination of data analysis and a simple numerical model we show that the key boundary layer dehumidifier is ageostrophic cross-channel sea breezes. This circulation develops semidiurnally in response to thermal gradients across the Red Sea's coasts because of disparate land-ocean heat capacities. During the summer day the thermally induced high-pressure center over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Sofianos et al [2002] estimated an annual mean evaporation rate of ∼2 m yr −1 for the Red Sea. Matsoukas et al [2007], using a radiation transfer model, estimated an annual evaporation rate of 2.1 ± 0.3 m yr −1 for the Red Sea, and a similar value was estimated for the northern Red Sea by Eshel and Heavens [2007]. These studies support an evaporation rate closer to ∼2 m yr −1 for the gulf unlike the commonly cited value of ∼3.5-4 m yr −1 that was estimated by Assaf and Kessler [1976].…”
Section: Appendix B: Surface Fluxesmentioning
(Expert classified)
“…Sofianos et al [2002] estimated an annual mean evaporation rate of ∼2 m yr −1 for the Red Sea. Matsoukas et al [2007], using a radiation transfer model, estimated an annual evaporation rate of 2.1 ± 0.3 m yr −1 for the Red Sea, and a similar value was estimated for the northern Red Sea by Eshel and Heavens [2007]. These studies support an evaporation rate closer to ∼2 m yr −1 for the gulf unlike the commonly cited value of ∼3.5-4 m yr −1 that was estimated by Assaf and Kessler [1976].…”
Section: Appendix B: Surface Fluxesmentioning
(Expert classified)
“…This result was expected since, in the Red Sea, salinity changes linearly along the north–south latitudinal gradient. Published datasets show that salinity in the Red Sea is relatively stable among years (Roik et al, ); nevertheless, oscillation in salinity can occur seasonally during the year as result of evaporation rates, precipitations and mixing of low saline surface inflow from Gulf of Aden (Eshel & Heavens, ; Sofianos, Johns, & Murray, ). Monitoring physio‐chemical variables for three reefs in the central Red Sea across 2 years, Roik et al () show that although salinity oscillations occur seasonally (up to 1.43), they are smaller in comparison to other reef systems affected by riverine and precipitation inputs, such as on inshore reefs in the Great Barrier Reef, where salinity can fluctuate from five to ten (Roik et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed association of P. lutea, P. lobata and P. harrisoni with C. thermophilum symbionts in the southern Arabian Gulf where SST (36°C) and salinity (42) (Roik et al, 2016); nevertheless, oscillation in salinity can occur seasonally during the year as result of evaporation rates, precipitations and mixing of low saline surface inflow from Gulf of Aden (Eshel & Heavens, 2007;Sofianos, Johns, & Murray, 2002).…”
Section: Symbiodiniaceae Biogeography Across Red Sea Gradientsmentioning
confidence: 99%
“…The Red Sea, a semienclosed marginal sea of the Indian Ocean located between 12 • N and 30 • N, is one of the saltiest and warmest water bodies on Earth and a primary source of high salinity waters for the oceanic intermediate layer (e.g., Beal et al, 2000;Han & McCreary, 2001). Intense air-sea interactions characterize the Red Sea, which has one of the highest evaporation rates of the global oceans, with an annual mean of 2.06 ± 0.22 m/year (Bower & Farrar, 2015;Eshel & Heavens, 2007;Sofianos et al, 2002;Tragou et al, 1999).…”
Section: Introductionmentioning
confidence: 99%